Parotidite aguda em adulto jovem sistemicamente saudável: relato de caso clínico - Molon, Rafael Scaf de [UNESP] (2012)
This study reports an unusual case of acute parotitis in a healthy young adult with good oral hygiene. Case Report: The patient sought the Department of Stomatology, at Ponta Grossa State University due to a swollen on the right parotid gland region. The patient underwent clinical and radiological treatments and was prescribed anti-inflammatory drugs and antibiotics. On the fifth day the signs and symptoms had disappeared. Conclusion: The development of acute parotitis in healthy young adults with good oral hygiene is possible, but this makes the diagnosis more difficult. Anti-inflammatory, antibiotic and heat physiotherapy can contribute to the recovery of the signs and symptoms after 5 days of treatment.